The clonal relationships between pre‐cancer and cancer revealed by ultra‐deep sequencing. Issue 3 (24th July 2015) - Wood, Henry M; Conway, Caroline; Daly, Catherine; Chalkley, Rebecca; Berri, Stefano; Senguven, Burcu; Stead, Lucy; Ross, Lisa; Egan, Philip; Chengot, Preetha; Graham, Jennifer; Sethi, Neeraj; et al.
Abstract The study of the relationships between pre‐cancer and cancer and identification of early driver mutations is becoming increasingly important as the value of molecular markers of early disease and personalised drug targets is recognized, especially now the extent of clonal heterogeneity in fully invasive disease is being realized. It has been assumed that pre‐cancerous lesions exhibit a fairly passive progression to invasive disease; the degree to which they, too, are heterogeneous is unknown. We performed ultra‐deep sequencing of thousands of selected mutations, together with copy number analysis, from multiple, matched pre‐invasive lesions, primary tumours and metastases from five patients with oral cancer, some with multiple primary tumours presenting either synchronously or metachronously, totalling 75 samples. This allowed the clonal relationships between the samples to be observed for each patient. We expose for the first time the unexpected variety and complexity of the relationships between this group of oral dysplasias and their associated carcinomas and, ultimately, the diversity of processes by which tumours are initiated, spread and metastasize. Instead of a series of genomic precursors of their adjacent invasive disease, we have shown dysplasia to be a distinct dynamic entity, refuting the belief that pre‐cancer and invasive tumours with a close spatial relationship always have linearly related genomes. We show that oral pre‐cancer exhibits considerable subclonal heterogeneity in its own right, that mutational changes in pre‐cancer do not predict the onset of invasion, and that the genomic pathway to invasion is neither unified nor predictable. Sequence data from this study have been deposited in the European Nucleotide Archive, Accession No. PRJEB6588. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.